Determining addition pathways and stable isomers for CF3 functionalization of endohedral Gd@C60. Issue 9 (5th September 2018) - Ewels, Chris; Rio, Jeremy; Niwa, Hiroyuki; Omachi, Haruka; Shinohara, Hisanori; Rayson, Mark; Briddon, Patrick
Abstract : Using density functional theory approaches, we follow the sequential addition of CF3 functional groups to the surface of the metallic endofullerene species Gd@C60 . The presence of gadolinium in the interior of the cage strongly influences the addition sequence. The calculations are able to successfully identify end points in the addition sequence at Gd@C60 (CF3 ) n, n = 3 and two isomers at n = 5, in predictive agreement with experiment. Inverting the algorithm to determine the most labile groups also identifies the correct positively charged Gd@ C 60 ( C F 3 ) 4 + isomer, as confirmed by experimental mass spectra. The importance of surface mobility, notably at later stage addition, is discussed.